COOPERATION BETWEEN EUROPEAN UNION MEMBER STATES IN THE FIELD OF CRIMINAL JUSTICE - Jakulin, Vid (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The author presents in his paper the competences and objectives of Eurojust, the functioning of this body and the cooperation of Eurojust with other agencies. Eurojust is a body of the European Union, whose task is to encourage and improve the coordination and cooperation between competent judicial authorities of Member States. This body has its legal personality and was established by the EU Council Decision in 2002. This Decision was amended in 2003 and 2009. Eurojust does not deal with all sorts of crime, because it was established with a view to reinforcing the fight against serious crime. The general competence of Eurojust covers all types of crime and offences in respect of which Europol is at all times competent. The competence of Europol is defined in the Article 4 of the EU Council Decision setting up the European Police Office (Europol) and in the Annex to this decision. Pursuant to this provision and its annex, the Europol is competent for organised crime, terrorism and other serious forms of crime, listed in the Annex to the Decision and which affect in such a degree two or more Member States that it urges, due to the extent, importance and consequences of criminal offences a joint action of Member States. In the Annex to the Decision are listed criminal offences which are within the competence of Europol and consequently also within the competence of Eurojust. Eurojust is competent for the offences on the territory of all Member States. Eurojust may assist also in criminal matters at the request of a Member State’s competent authority in which is involved a non-Member State, but only in the case when an agreement establishing cooperation with a non-Member state has been concluded or when this assistance is absolutely necessary. In the context of its functioning, Eurojust pursues the following objectives: (a) to stimulate and improve the coordination between the competent authorities of the Member States in the investigations and prosecutions in the Member States, taking into account any request emanating from a competent authority of a MemberState and any information provided by any body competent by virtue of provisions adopted within the framework of the Treaties; (b) to improve cooperation between the competent authorities of the Member States, in particular by facilitating the execution of international mutual legal assistance and the implementation of legal instruments which implement the principle of the mutual recognition; (c) to support otherwise the competent authorities of the Member States in order to render their investigations and prosecutions more effective. Eurojust is composed of 28 members who consists the College. Eurojust is composed of one national member seconded by each MemberState in accordance with its legal system, being a prosecutor, judge or police officer of equivalent competence. Member States have to ensure a continual and efficient participation in achieving objectives of Eurojust pursuant to Article 3. Eurojust has proved successful since its establishment and has gained a high degree of trust among the Member States. It is important that it enables besides the cooperation between the Member States also the cooperation with the institutions, authorities and agencies of the European Union and also the cooperation with the third states (non-Members) and organisations. It has to be specially stressed that the cooperation between different organisations and states in the prosecution of international crime is of utmost importance.